Determination of Beta-carrot Levels of Campolay Fruit (Pouteria campechiana) by Method HPLC - Yusuf Irfan; Andini Putri Riandani; Anita Suri; Mutiah Aulia Amali (Syntax Idea)
Besides its sensory characteristics, campolay fruit has the potential to be functional food. The yellow color of campolay fruit indicates the presence of carotenoids. One highly beneficial group of carotenoids is beta-carotene, which is abundantly available in agricultural products and makes this compound one of the most advantageous components in the prevention and treatment of various types of eye diseases. HPLC, which stands for High-Performance Liquid Chromatography, is a chemical analysis technique used to separate, identify, and measure the components in a solution mixture. The beta-carotene testing process in campolay fruit is conducted using High-Performance Liquid Chromatography (HPLC) equipment with a visible light detector at a wavelength of 446 nm. From the HPLC analysis, the regression equation obtained is y = 366032x - 6388. From the standard beta-carotene solution, a linear relationship between absorbance and concentration was obtained with a correlation coefficient (r) of 0.9996. The peak area of the campolay fruit extract was obtained. The sample concentration is calculated by comparing the peak area of the sample with the peak area of the standard beta-carotene, resulting in the beta-carotene concentration of the campolay fruit extract using the high-performance liquid chromatography method. Based on the beta-carotene concentration of the campolay fruit obtained from this study, it can be concluded that the beta-carotene concentration of the campolay fruit is 0.15 mg/L